2010
DOI: 10.1111/j.1540-8183.2010.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Plaque Modification with Rotational Atherectomy and/or Cutting Balloon before Drug‐Eluting Stent Implantation for the Treatment of Calcified Coronary Lesions

Abstract: In this population at high risk of restenosis, aggressive PM by CB and/or RA before DES implantation provides excellent mid-term outcomes with only 3.4% TLR and 2.1% ST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 34 publications
3
27
0
2
Order By: Relevance
“…Rates of periprocedural complications in the literature range from 1.6 to 14.4% whilst vascular access complications range from 1.6 to 5.8% . In our multicentre, observational study we have confirmed the low rates of periprocedural (6.4%) and vascular access complications (1.9%), in a high‐risk, all‐comers population.…”
Section: Discussionsupporting
confidence: 80%
“…Rates of periprocedural complications in the literature range from 1.6 to 14.4% whilst vascular access complications range from 1.6 to 5.8% . In our multicentre, observational study we have confirmed the low rates of periprocedural (6.4%) and vascular access complications (1.9%), in a high‐risk, all‐comers population.…”
Section: Discussionsupporting
confidence: 80%
“…1) Several devices such as those used in directional coronary atherectomy, 6) RA, [7][8][9][10][11] and cutting balloon [10][11][12] for calcified lesions have been proposed to achieve optimal dilation prior to stent implantation. However, it is occasionally difficult to achieve dilation because of the presence of a heavy calcified plaque even after RA.…”
Section: Discussionmentioning
confidence: 99%
“…Rotational atherectomy is reasonable for fibrotic or heavily calcified lesions that might not be crossed by a balloon catheter or adequately dilated before stent implantation (258,259,395). …”
Section: Class Iiamentioning
confidence: 99%